Are Risk Preferences Stable across Contexts? Evidence from Insurance Data - Barseghyan, Levon; Prince, Jeffrey; Teitelbaum, Joshua C (American Economic Review, 2011)
Using a unique dataset, we test whether households' deductible choices in auto and home insurance reflect stable risk preferences. Our test relies on a structural model that assumes households are objective expected utility maximizers and claims are generated by household-coverage specific Poisson processes. We find that the hypothesis of stable risk preferences is rejected by the data. Our analysis suggests that many households exhibit greater risk aversion in their home deductible choices than their auto deductible choices. Our results are robust to several alternative modeling assumptions. (JEL D11, D83)